Vortex Induced Vibration (VIV) Reduction Measure on Dimpled Concrete Coated Pipeline - SAZALI, SYAZWAN (IRC, 2016)
Pipelines due to high current and dynamic seabed topography, are expose to free spanning and eventually leads to VIV formation. Effective VIV suppression device are sought that will mitigate VIV and reduce drag for operation application. One of the ways to reduce the VIV is to adapt dimple onto the concrete coating of the marine pipeline. In this study, CFD analysis will be carry out for three cases which one of a regular pipeline, then for a pipeline attached with marine fairings and one with dimpled concrete coating pipeline. The motivation of doing such arrangement is to analyse the efficiency of the dimple geometry arrangement in order to suppress the vortex-induced vibration (VIV) of the corresponding marine pipeline.